Different nitrogen uptake patterns of plant and soil microorganisms in the forest-grassland transition zone on the Loess Plateau - Wang, Lina; Deng, Xu; Zhou, Ying; Geng, Xueqi; Zhang, Zeling; Tang, Yakun (Frontiers in Plant Science, 2025)
IntroductionIt is unclear whether plants and microorganisms achieve niche complementarity by taking up different inorganic nitrogen (N) forms to alleviate N competition, particularly in N–limited regions.MethodsThis paper conducted a 15-day 15N tracer study (15NH4NO3 or 15NH4NO3) in situ to quantitatively calculate the uptake rates of plants and microorganisms in four stands (pure Hippophae rhamnoides L, pure Pinus tabuliformis Carrière, mixed H. rhamnoides–P. tabuliformis, and Artemisia gmelinii Weber ex Stechm grassland) in the forest–grassland transition zone on the Loess Plateau during the growing season. Among them, H. rhamnoides and P. tabuliformis can associated with arbuscular mycorrhizal and ectomycorrhizal, respectively.ResultsThe results indicated that H. rhamnoides in the pure stand and A. gmelinii preferred to take up 15NO3–, whereas P. tabuliformis in the pure stand preferred 15NH4+. Compared to pure stands, mixed afforestation decreased the NH4+ and NO3– uptake rate of H. rhamnoides by 87% and 70%, respectively, but did not alter the N preference of plants. Plants and microorganisms differed in their N preferences in the pure stand, whereas this was not the case in the mixed stand. The proportional similarity index between H. rhamnoides and P. tabuliformis (0.90 ± 0.01) was higher than that between plants and microorganisms in forest stands, except for P. tabuliformis and microorganisms in the mixed stand (0.90 ± 0.02).DiscussionThose results indicated that niche complementarity by preferring different N forms can alleviate N competition. This study helped to gain a deeper understanding of the plasticity of N uptake patterns by plants and microorganisms in the forest–grassland transition zone, and provides theoretical support for vegetation restoration during the implementation of the Grain for Green program on the Loess Plateau.